An Innovative Ventricular Assist Device Strategy as a Bridge-to-Recovery in an Infant with Glenn Physiology. Issue 3 (March 2019) - Boston, Umar; Sun, John X.; Kumar, T. K. Susheel; Knott-Craig, Christopher
Abstract : Mechanical circulatory support for infants with single ventricle physiology remains challenging. Utilization of a ventricular assist device (VAD) has potential advantages over extracorporeal circulatory membrane oxygenation. As such, VAD utilization in single ventricle patients with refractory heart failure continues to be explored. Herein, we describe a novel VAD strategy to support an infant with Glenn physiology who presented in cardiogenic shock related to myocardial depression of unknown etiology. This VAD configuration supported the systemic circulation independent of the Glenn circulation. Seven days of VAD support resulted in recovery of myocardial and end-organ function leading to VAD removal. The patient remains alive and free from transplantation 16 months post VAD explantation. Abstract : Supplemental Digital Content is available in the text.